Daniela Stavělová: Červená růžičko, proč se nerozvíjíš. Doudlebská masopustní koleda: tanec, identita, status a integrace. [Red Rose, Why Don’t You Thrive. A Carnival Carol from Doudleby: Dance, Identity, Status and Integration]: Prague, The Institute of Ethnology of the Academy of Sciences of the Czech Republic + Association for Children’s Creativity in Dance, 2008, 85 pages + DVD - Jurková, Zuzana (Lidé města, 2009)
A review of the book by Daniela Stavělová.